Factors predicting in‐hospital mortality among patients admitted with community acquired pneumonia at a tertiary care hospital Karachi, Pakistan. (2nd January 2020) - Iqbal, Nousheen; Irfan, Muhammad; Siddique, Faraz; Arshad, Verda; Zubairi, Ali Bin Sarwar
Abstract: Introduction: Community Acquired Pneumonia (CAP) is associated with significant morbidity and mortality globally, but unfortunately there is limited data available from South East Asia. Objective: To determine the risk factors associated with in‐hospital mortality in patients with CAP in a tertiary care hospital of Pakistan. Methods: A retrospective study was conducted on adult patients admitted with a diagnosis of CAP from January 2011 till December 2016. Their clinical records were reviewed and a multivariable analysis was done to determine the factors associated with in‐hospital mortality. Results: A total of 1100 files were reviewed, of which 509 were included in the analysis. The mean age was 63.6 ± 16.5 years and 302 (52.16%) were males. The most Common isolated pathogen was Staphylococcus aureus (23%) . Overall mortality was 10.8%. On univariate analysis factors associated with mortality were old age patients ( P  = 0.02); history of pneumonia in last 12 months ( P  = 0.008); CURB 65 score ≥ 3 ( P  < 0.001) and high dependency units as initial site of care ( P  < 0.001). On multivariable analysis CURB65 ≥ 3 score; high dependency unit as initial site of care; bedridden status; presence of bilateral infiltrates on chest X‐ray and hemoglobin of 10.4 g/dL or less at the time of admission were key determinants of in‐hospital mortality. Conclusion: We found CURB65 ≥ 3 score; high dependency unit as initial site of care; bedridden status; bilateral infiltrates on chest X‐ray and low hemoglobin (10.4 g/dL or less) at the time of admission as independent risk factors of in‐hospital mortality. Staphylococcus aureus was the most common organism isolated in patients.